PENGEMBANGAN INSTRUMEN TES BERDASARKAN KOMPONEN PROSES LITERASI MATEMATIKA - rusmining rusmining; Burhanudin Arif Nurnugroho (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
This development research aims to develop a mathematical literacy test instrument for vector material. The research stages use the four D development model, namely define, design, develop, and disseminate, while the data analysis is qualitatively descriptive. In the define stage, a preliminary study was conducted to determine the characteristics of students and the previous test questions instruments. At the design stage, an instrument for the description of vector material based on mathematical literacy was compiled. At the develop stage, the validation process of three expert validators is carried out as well as testing of limited scale questions, namely small and large scale. The instrument is said to be feasible if it is valid and practical. The instrument is valid if the results of the category validation are at least good. And practical instruments if the results of the questionnaire category are at least good. The results of the validation obtained assessments, namely: (1) the average value of validator 1 is 4.17 valid with good category; (2) the average value of validator 2 is 4.52 valid with a very good category; and (3) the average value of validator 3 is 4.47 valid with a very good category. While the results of the questionnaire include: (1) a small-scale trial obtained an average result of 3.54 which means that the practical instrument is in the very good category. (2) large-scale trials obtained an average result of 3.38, meaning that the practical instrument was in good category. From these results, it is concluded that the test instrument developed is valid and practical.